The Influence of Tun Dr. Mahathir’s leadership style towards students association leaders in UiTM Sarawak Campus Samarahan/ Nur Aqeela Abd Rahman & Abang Muhamad Zulfadhli Abang Ariffin - Abd Rahman, Nur Aqeela; Zulfadhli Abang Ariffin, Abang Muhamad (2016)
This chapter provide a review of the literature on Tun Dr Mahathir Mohamad background, early political career and his contribution towards nation. This chapter also provide review adoption of leadership theories and influence of Tun Dr Mahathir’s leadership towards student’s association leaders in UiTM Sarawak Campus Samarahan that have been identified in the research objective.